Pullout Strength of Graphene and Carbon Nanotube/Epoxy Composites - Saavedra-Flores, E (Elsevier Ltd, 2016)
An atomistic multiscale modelling approach is used to simulate the nonlinear pullout behaviour of interlinked single walled carbon nano tubes (SWCNT) and single layer graphene sheets (SLGS) embedded in an epoxy polymer. The pullout forces have been computed for various configurations of nanocomposites (SWCNT-SWCNT, SLGS-SLGS and hybrid SLGS-SWCNT), also by evaluating the effect provided by three different interlink compounds. The interfacial strength due to fibre pullout predicted by the hybrid atomistic-FE model is compared against experimental and molecular dynamics results available in open literature. The results show the specific deformation characteristics (localised auxetics) that provide an increase of pullout forces and interfacial strength with the use of the links. © 2016 Elsevier Ltd